LUX-Lung 5 - Misra-Press, Anita (MD Conference Express, 2015)
LUX-Lung 5 is the first prospective randomized, phase 3 trial to demonstrate superior progression-free survival by continuing afatinib plus paclitaxel as fourth-line treatment vs single-agent chemotherapy in patients with non–small cell lung cancer who had disease progression on chemotherapy with the combination of erlotinib plus gefitinib and with afatinib monotherapy with a manageable safety profile.